Primary decompressive craniectomy in neurocritical patients. a meta-analysis of randomized controlled trials, cohort and case-control studies - Muñoz, Javier; Keough, Elena Aurea; Barrios, Juan Camilo; Fernández, Nerio José; Dalorzo, Mario Guillermo; Visedo, Lourdes Carmen (Journal of Emergency and Critical Care Medicine, 2018)
Background: Primary decompressive craniectomy (DC) is increasingly used in certain neurosurgical pathologies. We have performed a systematic review and meta-analysis to study the results in terms of quality of life (QOL) and survival at 1 year of follow-up of patients undergoing this treatment. Methods: Meta-analysis of randomized controlled trials, cohort and case-control studies. Results: Fifteen studies (1,603 patients) were included (9 ischemic stroke, 3 trauma brain injury, 3 subarachnoid hemorrhage, none cerebral hemorrhage). None of the studies used specific QOL assessments. Eleven studies reported modified Rankin Scale and 4 Extended Glasgow Outcome Scale. DC reduces mortality or vegetative state (OR 0.21; 95% CI, 0.14–0.32) and the combined goal of mortality or moderate-severe disability (OR 0.35; 95% CI, 0.21–0.58) at 12 months in a malignant stroke of the middle cerebral artery (MCA). Patients ≤60 years, with infarctions ≥50% of MCA territory, without contralateral involvement, Glasgow Coma Score ≥6 and without bilateral fixed mydriasis, should be considered for early DC. However, international records indicate that a different population is being treated with DC. Those beneficial effects cannot be demonstrated in the other studied pathologies. As rule, the medical protocols do not include monitoring of oxygenation of brain tissue, cerebral microdialysis or electroencephalogram (EEG)-derived parameters. Conclusions: The only clear current indication refers to certain select cases of malignant MCA infarction. Future studies should incorporate the evaluation of QOL, the institutional coverage and rehabilitation services, economic analysis, and impact of modern neuromonitoring techniques. Also, it seems that we should ensure that real clinical indications conform to those evaluated in clinical trials.